Learning Management System Development with Application of Asynchronous Learning Method in STMIK IBBI Medan - Marwa Halim; Suharjito Suharjito (CommIT (Communication and Information Technology) Journal, 2015)
This article will explain asynchronous learn- ing system using attractive discussion forums and video teaching materials features for user so that the devel- opment of both features will increase e-learning system usage by students and lecturers which can eventually im- prove the students’ absorption on the provided teaching materials, increase the active participation of students, improve self-learning ability, and to improve the quality of learning materials. The method used in this study by distributing questionnaires in online form to stakeholders users consisting of lecturers and students with the num- ber of respondents is 225 people and author use model ADDIE which focuses on Analysis, Design, Development, Implementation and Evaluation as development design. Results of this study is an application of web-based asynchronous learning which can be used by students and lecturers with the results of the application evaluation is based on a survey to students and lecturers. From this study, can be concluded that to support online learning with asynchronous method using the video learning feature in online lecture needs to be developed in order to support the science transformation process from lecturers to students. Attractive video teaching  materials  model for students has characteristics such as screen shots and presentation models.